2016
DOI: 10.1371/journal.pone.0168081
|View full text |Cite
|
Sign up to set email alerts
|

Dry Eye after Small Incision Lenticule Extraction (SMILE) versus Femtosecond Laser-Assisted in Situ Keratomileusis (FS-LASIK) for Myopia: A Meta-Analysis

Abstract: PurposeTo compare dry eye after small incision lenticule extraction (SMILE) and femtosecond laser-assisted LASIK (FS-LASIK) for correcting myopia.MethodsCENTRAL, Embase and PubMed were searched in November 2016. All randomized controlled trials (RCTs) and prospective cohorts that compared dry eye after SMILE with FS-LASIK were selected.ResultsFive cohorts and one RCT were identified for comparing dry eye after SMILE (291 eyes) and FS-LASIK (277 eyes). The pooled results revealed that the SMILE and FS-LASIK gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 32 publications
1
31
0
Order By: Relevance
“…We consider a procedure of the ReLEx SMILE type to be a method with a lesser influence on the quality of the lachrymal film, with a quicker return to the original values of osmolarity and potentially greater comfort for the patient malised in the group of patients who had undergone ReLEx SMILE. The ST value remained worsened in both groups, in the FS-LASIK group the OSDI also remained worsened [17].…”
Section: Resultsmentioning
confidence: 82%
“…We consider a procedure of the ReLEx SMILE type to be a method with a lesser influence on the quality of the lachrymal film, with a quicker return to the original values of osmolarity and potentially greater comfort for the patient malised in the group of patients who had undergone ReLEx SMILE. The ST value remained worsened in both groups, in the FS-LASIK group the OSDI also remained worsened [17].…”
Section: Resultsmentioning
confidence: 82%
“…This is in good accordance with the previously published literature. 8 12 Since 2016, five meta-analyses 8 12 have been conducted to assess possible differences in clinical outcomes when FS-LASIK and SMILE were used to correct myopia and myopic astigmatism, showing that FS-LASIK and SMILE were comparable in terms of efficacy, predictability, and safety. 8 , 9 However, it is noteworthy that there are only few studies, which have been conducted on patient satisfaction and dry eye symptoms with a self-reporting questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“… 8 11 According to one recent meta-analysis, SMILE does not show superiority over FS-LASIK with similar and acceptable objective parameters, but SMILE may have milder subjective symptoms. 12 In this study, we investigated the factors affecting patient satisfaction in subjects who underwent FS-LASIK or SMILE for myopic eyes. Dry eye symptoms and patient satisfaction were reported in this real-life situation study in the self-questionnaire based on the visual analog scale (VAS) grading.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies, including meta-analyses, found that SMILE is less invasive to the corneal nerves and reduces the incidence of postoperative dry eye compared to femtosecond LASIK. [28][29][30] In these studies, dry eye symptoms and TBUT were significantly better in SMILE; however, the Schirmer values and tear osmolality did not differ between LASIK and SMILE. The postoperative tear secretion after SMILE determined by the Schirmer test varied among the previous studies.…”
Section: Mechanisms Involved In Post-lasik Dry Eyementioning
confidence: 98%